Sustainable Development of Urban Rail Transit Resources Development - Sun, Xianke; Huang, Yujuan; Wang, Xiaoping; Zhu, Xiaolei (Journal of Theory and Practice of Engineering Science, 2023)
Urban rail transit system is characterized by high efficiency, good quality, safety and convenience. In the current process of socio-economic development, urban rail transit has become an important component of urban transportation. The acceleration of urbanization in China has promoted the improvement of current urban rail transit technology, and provided high-quality services to alleviate current urban traffic congestion. In the development process of urban rail transit, it presents characteristics such as high operating costs and high investment. It is necessary to choose a reasonable market-oriented development model based on the actual situation to improve the overall economic and social benefits of urban rail transit.